Analysis of the Similarities between Islamic Government Systems and Modern State Government Systems - Dzar, Muhammad Abu (NEGREI: Academic Journal of Law and Governance, 2023)
The purpose of this study is to get an idea of how the principles in Islamic and modern government systems compare, both similarities and differences. Researchers use descriptive-qualitative research. Data obtained through literature reading, analyzed and critically compromised for further narrative description. This research uses descriptive-qualitative analysis, data and information about matters related to this research are studied, reviewed, classified carefully, then the analysis process is carried out by deduction, the analysis process takes place continuously from beginning to end with the aim of finding answers to the rumplations of problems carried by the research.  Based on the analysis of this research data concludes that  the leader in the early Islamic and contemporary government system is a powerful and influential figure, the establishment of the State of Medina on the basis of the agreement of diverse nations, this is the same as the establishment of many countries in the world today, the State of Medina is a state of law because it has a Medina Charter or Medina Constitution,  as many countries in the world declare as State of law. Muhammad as a central figure has always been open in accepting the opinions of others for the benefit of the country, his style of government is fiber with domocracy. Muhammad also at one time became the leader of the State as well as the leader of the government and had full authority just like  the current presidential system of government.